2019
DOI: 10.2147/ott.s217019
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiR-223-3p targeting epithelial cell transforming sequence 2 oncogene inhibits the activity, apoptosis, invasion and migration of MDA-MB-468 breast cancer cells</p>

Abstract: PurposeThis research was to investigate the role of miR-223-3p targeting epithelial cell transforming sequence 2 oncogene (ECT2) in activity, apoptosis, invasion and migration of MDA-MB-468 breast cancer (BC) cells.MethodsThe human BC cell lines MDA-MB-468 were used for the experiment. They were divided into six groups: blank group (no plasmid transfection), NC group (negative control, transfected empty plasmid), miR-223-3p mimic group (transfected miR-223-3p mimic plasmid), miR-223-3p inhibitor group (transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
(26 reference statements)
0
25
0
Order By: Relevance
“…**P < .01 and ***P < .001 vs healthy controls, Student's t test several tumour types and is known to be involved in regulating cell growth and apoptosis. 25,26 Furthermore, previous studies have shown that miR-223-3p has the ability to dampen the inflammatory response. 27,28 However, its role in syphilis is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…**P < .01 and ***P < .001 vs healthy controls, Student's t test several tumour types and is known to be involved in regulating cell growth and apoptosis. 25,26 Furthermore, previous studies have shown that miR-223-3p has the ability to dampen the inflammatory response. 27,28 However, its role in syphilis is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, miRNAs have emerged as an important therapeutic target for many diseases, including metabolic diseases, inflammation and cancer. MiR‐223‐3p was found to be down‐regulated in several tumour types and is known to be involved in regulating cell growth and apoptosis 25,26 . Furthermore, previous studies have shown that miR‐223‐3p has the ability to dampen the inflammatory response 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidences show that miR-223 is a tumor suppressor gene in breast cancer. One of the studies reported that miR-223 regulates cancer cell invasion and migration through targeting ECT2 ( 34 ). Fabris et al showed that miR-223 could inhibit the recurrence of breast cancer by mediating the EGF signaling pathway in their study ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that hsa-miR-223-3p and hsa-miR-365a-3p could promote proliferation, migration and invasion of cancer cells [ 28 31 ]. But what very interesting is that previous studies also indicated that hsa-miR-223-3p and hsa-miR-365a-3p could inhibit the invasion and migration of cancer cells [ 32 35 ]. All of those results suggested that the same gene or miRNA may play different roles in different cancers.…”
Section: Discussionmentioning
confidence: 99%